Branding dan Pemasaran Digital sebagai Upaya Pemberdayaan UMKM Ropunk - Santi Rimadias; Renata Zahra; Mutiya Riszki Awalia; Athaillah Rafi Sakhaa; Amara Sahira; Muhammad Raihan Khadavi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth, creating jobs, and improving community well-being. In today's digital context, the use of branding and digital marketing has become a powerful approach to strengthening MSME competitiveness. This community service activity aims to provide digital marketing assistance to Ropunk, an MSME focused on the culinary sector, specializing in 30 cm-long bread. The methods employed included observation, interviews, and digital marketing optimization, including assistance with managing their Instagram account. Findings from this community service program indicate that prior to the assistance, Ropunk's digital marketing activities were not optimal, reflected in a lack of consistent content, unorganized visual design, and low customer interaction. Through the assistance process, social media management, visual design development for content, and the development of a comprehensive digital marketing strategy were implemented. Consequently, there has been an improvement in the quality of social media displays, consistency in content uploads, and the potential for increased interaction and market reach. In conclusion, implementing appropriate branding and digital marketing strategies can increase brand awareness, expand market share, and strengthen the competitiveness of MSMEs sustainably. Therefore, maintaining consistency in social media management is crucial for achieving sustainable and optimal results in the long term.